Influence of Cortical Comminution and Intra-articular Involvement in Distal Radius Fractures on Clinical Outcome: A Prospective Multicenter Study - Wadsten, Mats Å; Buttazzoni, Gunnar G.; Sjödén, Göran O.; Kadum, Bakir; Sayed-Noor, Arkan S. (Journal of Wrist Surgery, 2017)
Aim The purpose of this prospective multicenter study was to test the predictive value of cortical comminution and intra-articular involvement on function and quality of life in distal radius fractures (DRFs) using the Buttazzoni's classification system.Patients and Methods We studied 406 patients between skeletal maturity and 74 years of age with DRF. Fractures with acceptable radiographic alignment were immobilized with a cast. Fractures with nonacceptable radiographic alignment underwent closed reduction and 4 to 6 weeks cast immobilization. Radiographs were obtained after reduction and at 10 to 14 days. Redisplaced fractures were offered surgical treatment. One-year follow-up included grip strength, range of motion (ROM), quickDASH, EQ-5D (including visual analog scale [VAS] for health status), and VAS pain.Results We found no statistically significant differences in QuickDASH, EQ-5D questionnaire, EQ-5D health status VAS, and VAS pain among the Buttazzoni classes. However, initial displacement was associated with worse quickDASH score, worse EQ-5D score, reduced grip strength, and reduced ROM. Dorsal comminution was associated with worse quickDASH score, reduced flexion, and reduced pronation–supination ability. Volar comminution predicted loss of extension, while intra-articular involvement was associated with reduced flexion–extension arc and worse EQ-5D score. There was a significant difference in ROM between noncomminuted and comminuted fracture classes.Conclusion Initial fracture position, type of comminution, and intra-articular involvement influenced the clinical outcome in DRF.
Keywords: distal radius fracture; wrist; classification; outcome; radiology